Constructional Borrowing From English in Hong Kong Cantonese - Chan, Brian Hok-Shing (Frontiers in Communication, 2022)
Previous research on Cantonese-English contact in Hong Kong has focused on lexical phenomena, primarily lexical borrowing and intra-sentential, single-word code-switching (or code-mixing). Although code-switching may also involve longer English phrases, the English elements are mostly inserted into Cantonese-framed sentences in accordance with the Matrix Language Frame/MLF Model (Myers-Scotton 1993). In other words, the syntax of Cantonese appears to be largely intact despite words or phrases drawn from English (Chan 1998; Leung 2000). This paper underscores that in fact English syntax can be melded more intricately with lexis from both Cantonese and English, thus defying the MLF Model; however, recurrent cases are limited to three constructions so far, namely, the which-relative (Leung 2000), the English PP-postmodifier (Chan 2015), and an [NP COP P NP] sequence with an English preposition (Chan 2018). A re-examination of these three constructions reveals that, rather than linguistic economy (Li 1999), they are semantically and pragmatically motivated to convey some specific meaning. Moreover, all these constructions are lexico-syntactic (Chan 2018; Li 1999) in the sense that they prototypically contain an English word, namely, the relativizer which, an English noun and an English preposition respectively. Accordingly, these cases can also be treated as code-switching, though structural borrowing better captures the fact that some English syntactic structure is transferred. In line with Construction Grammar (Croft 1991), these constructions are better understood as constructional borrowing in which each construction as a whole – composed of not only words from Cantonese and English but also a syntactic structure – conveys specific meaning. As for why such cases of structural or constructional borrowing are limited or partial, this paper suggests that it is more due to a soft constraint that separates English and Cantonese grammars – Hong Kong speakers still tend to convey a sense that they speak Cantonese among themselves – although they draw on linguistic resources from English. In this light, the Borrowability Hierarchy (Thomason and Kaufmann 1988) may be recast as a continuum of language separation and fluidity, which offers a more nuanced view to translanguaging.